Personal Integrity of Islamic Counselor on Professional Ethics Commitment - Haryati, Asti (Islamic Guidance and Counseling Journal, 2018)
A system, method, technique, or scientific competence will not be efficient as long as it is not done by a counselor who has a personal quality and integrity. Ethics, behaviors and good personality which appropriate to Islamic Sharia values should be improved to make a qualified Islamic counselor. An Islamic counselor with integrity means an honest person with a strong character, including consistency in all actions. A counselor who has integrity toward commitment will be able to show a good performance on duties and accordance with the authority within the value and professional ethics. In this article, author will attempt to describe what is personal of counselor that can support the effectiveness of the guidance and counseling services, the professional ethics of counselor that provided by the guidance and counseling profession organization, and personal integrity that can be seen from the words and actions that counselor do in the daily life.